Applicability of Kd for modelling dissolved 137Cs concentrations in Fukushima river water: Case study of the upstream Ota River. (April 2018) - Sakuma, Kazuyuki; Tsuji, Hideki; Hayashi, Seiji; Funaki, Hironori; Malins, Alex; Yoshimura, Kazuya; Kurikami, Hiroshi; Kitamura, Akihiro; Iijima, Kazuki; Hosomi, Masaaki
Abstract: A study is presented on the applicability of the distribution coefficient ( K d ) absorption/desorption model to simulate dissolved 137 Cs concentrations in Fukushima river water. The upstream Ota River basin was simulated using GEneral-purpose Terrestrial Fluid-flow Simulator (GETFLOWS) for the period 1 January 2014 to 31 December 2015. Good agreement was obtained between the simulations and observations on water and suspended sediment fluxes, and on particulate bound 137 Cs concentrations under both base and high flow conditions. By contrast the measured concentrations of dissolved 137 Cs in the river water were much harder to reproduce with the simulations. By tuning the K d values for large particles, it was possible to reproduce the mean dissolved 137 Cs concentrations during base flow periods (observation: 0.32 Bq/L, simulation: 0.36 Bq/L). However neither the seasonal variability in the base flow dissolved 137 Cs concentrations (0.14–0.53 Bq/L), nor the peaks in concentration that occurred during storms (0.18–0.88 Bq/L, mean: 0.55 Bq/L), could be reproduced with realistic simulation parameters. These discrepancies may be explained by microbial action and leaching from organic matter in forest litter providing an additional input of dissolved 137 Cs to rivers, particularly over summer, and limitations of the K d absorption/desorption model. It is recommended that future studies investigate these issues in order to improve simulations of dissolved 137 Cs concentrations in Fukushima rivers. Highlights: Study on validity of using the K d absorption/desorption model for simulating dissolved 137 Cs levels in a Fukushima river. Agreement generally good between simulations and observations for water, sediment and particulate 137 Cs discharge. Tuning of K d values for large particles was necessary to reproduce typical base flow dissolved 137 Cs concentrations. Simulations underestimated the seasonal variability of dissolved 137 Cs concentrations and peaks during heavy rainfall.